Efek Efek Pemberian Pakan Tambahan Berbasis Buah Pisang Tongka Langit terhadap Kandungan β-Karotena Madu Lebah Apis cerana (F.) - Masela, Efer Simon; Lamerkabel, Jacobus Suruka Aifaman; Riupassa, Pieter Agusthinus; Hiariej, Adriana (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Suplementary feed based on the flesh of tongka langit bananas has never been done, even though tongka langit bananas are very qualified as supplementary feed because there is 55% glucose as a substitute for nectar and other similar ingredients and the presence of β-carotene in these bananas as a precursor of vitamin A which is expected to be present in honey when given additional feed based on tongka langit banana. This study aims to determine the effect of giving tongka langit banana-based supplementary feed on the β-carotene content of Apis cerana (F.) bee honey. The research method used was experimental with a Completely Randomized Design at the A. cerana bee farm to obtain data related to feed consumption in four treatments located in Eri Village, Nusaniwe District, Ambon City, Maluku. Then the composition of honey in the form of β-Carotene and vitamin C was further analyzed using the KCKT method of normal phase chromatography (normal phase chromatography) related to the concentration of the four treatments at the Laboratory of the Bogor Agricultural Postharvest Research and Development Center. The results of the analysis of β-carotene content using the HPLC method showed that the highest β-carotene content was in the tongka langit banana feed of 2.275 mg/100g followed by fresh ripe tongka langit bananas of 2.198 mg/100g while in the water + sugar diet it was 2.075 mg/100g and natural feed without treatment as the lowest β-carotene content, namely 1.975 mg/100g. Keywords: Apis cerana, Tongka Langit Banana, Honey, β-Carotene, HPLC